Understanding the Relationship and Consensus of Religion, Spirituality and Counselling - Md. Yusoff, Yusmini (Jurnal Usuluddin, 2008)
There has long been an interest in the relationship between religious spirituality and mental health. However, this interest has extended to the use of traditional scientific methods for examining this relationship. The use of this method to examine spiritual and professional knowledge has provoked critical discussions among researchers because the philosophy of the traditional method may conflict with the theoretical assumptions of many conceptions of religion and spirituality. This conflict could lead to unintended and unfortunate consequences. This article attempts to explore these issues and therefore, I begin by presenting the foundation of the theoretical discussion and empirical work in the important realm of religion and spirituality. Then, I will outline the intersection and interaction between these values and counselling.